Transfer Knowledge: Submit Artikel Pada Jurnal Online Berbasis OJS Untuk IPELMAS - Triyanto Triyanto; Nodi Marefanda; Arfriani Maifizar; Nurkhalis Nurkhalis; Akmal Saputra; Rahma Husna Yana; Yeni Sri Lestari (Jurnal Pengabdian Masyarakat: Darma Bakti Teuku Umar, 2020)
The existence and quality of higher education nowadays can be influenced by the high and low levels of scientific work owned by lecturers and students. This scientific work becomes very important in the existence and quality of tertiary institutions because it's ranking at the national and international level is calculated on the ownership of the scientific work. So it is not surprising that BAN-PT as an external quality assurance institution which also has the task of assessing the accreditation of higher education also includes its assessment on this matter. Thus higher education that is technically operational at the study program level also pressures lecturers and students to be productive, which is to produce as much scientific work as possible. Even some lecturers provide requirements for students to write a scientific paper when they want to propose a thesis session. However, the number of scientific works owned by lecturers and students will not mean anything when not published in a journal that uses an open journal system. This emphasis lies in the open journal system, where the meaning will be far different from online journals. In general, not many students understand how to submit scientific papers in the form of articles to the open journal system there are still many lecturers who do not understand the process in the open journal system. For this reason, knowledge transfer in the form of technical training to submit articles in the online journal system is carried out. The main goal is to provide knowledge and insight into submitting articles. The results of the activity show the progress of understanding and knowledge, this is proven by simulations through the application of OJS version 2 which is used for the training process by the participants.